2019
DOI: 10.3390/su11236541
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Urban Functional Regions Based on Floating Car Track Data and POI Data

Abstract: Along with the rapid development of China’s economy as well as the continuing urbanization, the internal spatial and functional structures of cities within this country are also gradually changing and restructuring. The study of functional region identification of a city is of great significance to the city’s functional cognition, spatial planning, economic development, human livability, and so forth. Backed by the emerging urban Big Data, and taking the traffic community as the smallest research unit, a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Scholars studied the functional structure of the city by mainly using POI data and proposing frameworks to identify the functional regions of a city. For instance, Long and Shen [33] and Yu et al [34] established a method to discover zones with different functions by combining POI data with smart card data and floating car track data, respectively. Yuan et al [35] proposed a framework for discovering functional zones in a city through the analysis of human mobility trajectories among regions and POIs within regions.…”
Section: Related Studiesmentioning
confidence: 99%
“…Scholars studied the functional structure of the city by mainly using POI data and proposing frameworks to identify the functional regions of a city. For instance, Long and Shen [33] and Yu et al [34] established a method to discover zones with different functions by combining POI data with smart card data and floating car track data, respectively. Yuan et al [35] proposed a framework for discovering functional zones in a city through the analysis of human mobility trajectories among regions and POIs within regions.…”
Section: Related Studiesmentioning
confidence: 99%
“…Tu et al (2018) discerned urban functional regions via combining with human activity metrics (i.e., in‐home activity, 0:00–6:00; working activity, 9:00–12:00 & 14:00–17:00; social activity) based on mobile phone positioning data as well as remote sensing images. Yu et al (2019) identified urban functional zones based on dynamic human activity, namely, combining with the taxi trajectory data for deriving passengers’ tempo‐spatial commuting characteristics. Liu et al (2020) identified urban functional regions concerning dynamic human activities as well as landscape features, based on crowdsourced data (i.e., POIs, taxi trajectory data etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [20] proposed a dynamic time warping (DTW) distance-based kmedoids method to delineate functional regions based on building-level social media data. Yu et al [21] identified functional regions through the clustering method according to the travel characteristics derived from the taxi data and utilized POI data to label functionality.…”
Section: Introductionmentioning
confidence: 99%